Radiation effects on SOI microrelays for space applications - Lozano, A.; Palumbo, F.; Alurralde, Martín Alejo (The Electrochemical Society, 2009)
Fil: Alurralde, Martín Alejo. Comisión Nacional de Energía Atómica. Departamento de Energía Solar; Argentina